Proceedings of the 5th International Workshop on Java Technologies for Real-Time and Embedded Systems - JTRES '07 2007
DOI: 10.1145/1288940.1288961
|View full text |Cite
|
Sign up to set email alerts
|

A design pattern for using non-developmental items in real-time Java

Abstract: This paper addresses the need to reduce the difficulties in developing time-constrained Java applications. We present a design pattern for a class of time-constrained real-time applications that allows developers to use (and re-use) Java code libraries and non-developmental items (NDI). The proposed design pattern simplifies the implementation of the timeconstrained tasks substantially by not requiring the use of no-heap real-time threads. We tested the design pattern with the Java RealTime System (RTS) 2.0 fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…For easy reference, we will describe briefly in this section our Shadow Design Pattern for real-time applications reported in [9,10], which is defined by the following two key features:…”
Section: The Shadow Design Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…For easy reference, we will describe briefly in this section our Shadow Design Pattern for real-time applications reported in [9,10], which is defined by the following two key features:…”
Section: The Shadow Design Patternmentioning
confidence: 99%
“…In [8], we concluded that it is preferable to use only the regular, heap-using real-time threads for a class of real-time applications whose computations must be terminated by their hard deadlines and have to return the best approximations to their clients if they cannot finish their computations by the deadlines; we developed a new design pattern, called the Shadow Design Pattern, for this class of applications. We described how well this design pattern works with the Sun Java Real-Time System (RTS) 2.0 in [9]. The key feature that makes the Shadow Design Pattern successful is the availability of the real-time garbage collector (RTGC) whose priority is assignable.…”
Section: Introductionmentioning
confidence: 99%